AWS certified SysOps administrator - associate (SOA-C02) - Sluga, Marko (Expert on cloud computing) (Exam cram (Pearson Education, Inc.), 2022)
AWS Certified SysOps Administrator Associate (SOA-C02) Exam Cram is an all-inclusive study guide designed to help you pass the updated version of the AWS Certified SysOps Administrator Associate exam. Prepare for test day success with complete coverage of exam objectives and topics, plus hundreds of realistic practice questions. Extensive prep tools include quizzes, Exam Alerts, and our essential last-minute review CramSheet. The powerful Pearson Test Prep practice software provides real-time assessment and feedback with two complete exams. Covers the critical information needed to score higher on your AWS Certified SysOps Administrator Associate (SOA-C02) exam! Demonstrate baseline AWS Well-Architected Framework knowledge to support and maintain AWS workloads Use AWS monitoring and logging services and remediate issues based on monitoring and availability metrics Implement scalability and elasticity for reliability and business continuity Use AWS services to provision, deploy, maintain, and automate cloud resources Implement and manage security controls to meet compliance policies and requirements Implement, configure, and troubleshoot network features and connectivity issues Identify and implement cost and performance optimization strategies Prepare for your exam with Pearson Test Prep Realistic practice questions and answers Comprehensive reporting and feedback Customized testing in study, practice exam, or flash card modes Complete coverage of AWS Certified SysOps Administrator Associate (SOA-C02) exam objectives.